Best Answer

the answer is 6 because of the order of operations. you must do the multiplication first

2x2+2=6

Q: What is 2 plus 2 x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

x2 + 3x + 2 factors into (x + 1) (x + 2)

-x2 + 6x + 16 = -(x2 - 6x - 16) = -(x - 8)(x + 2) = -(8 - x)(x + 2)

x2 + 4x + 6 can not be factored. If you want, you can reduce it to an expression with a single x term by comleting the square: x2 + 4x + 6 = x2 + 4x + 4 + 2 = (x + 2)2 + 2

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}

Related questions

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

x4 +x2 =x2 (x2+1)

(x2 + 14x + 49) = (x + 7)2

x2 + 3x + 2 factors into (x + 1) (x + 2)

-x2 + 6x + 16 = -(x2 - 6x - 16) = -(x - 8)(x + 2) = -(8 - x)(x + 2)

If you have an equation of x2 plus x2, it is the same as saying 2 times x plus 2 times x. This can be written as 2x + 2x or x2 + x2. It is the same, then, as 4x. For example, if x equals 5: 2(5) + 2(5) = 10 + 10 = 20. 20 also equals 4(5).

(xn+2-1)/(x2-1)ExplanationLet Y=1+x2+x4+...+xn. Now notice that:Y=1+x2+x4+...+xn=x2(1+x2+x4+...+xn-2)+1Y+xn+2=x2(1+x2+x4+...+xn-2+xn)+1Y+xn+2=x2*Y+1Y+xn+2-x2*Y=1Y-x2*Y=1-xn+2Y(1-x2)=1-xn+2Y=(1-xn+2)/(1-x2)=(xn+2-1)/(x2-1)

X2+y2=25 (x-8)2+y2 =41

x2 - 2 + 4 = x2 + 2This term can not be factored any further

x2 + 4x + 6 can not be factored. If you want, you can reduce it to an expression with a single x term by comleting the square: x2 + 4x + 6 = x2 + 4x + 4 + 2 = (x + 2)2 + 2

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}

x2 + 26x + 48 = (x + 24)(x + 2)